2021
DOI: 10.1186/s12864-020-07337-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis uncovers roles of hydrogen sulfide for alleviating cadmium toxicity in Tetrahymena thermophila

Abstract: Background Cadmium (Cd) is a nonessential heavy metal with potentially deleterious effects on different organisms. The organisms have evolved sophisticated defense system to alleviate heavy metal toxicity. Hydrogen sulfide (H2S) effectively alleviates heavy metal toxicity in plants and reduces oxidative stress in mammals. However, the function of H2S for alleviating heavy metal toxicity in aquatic organisms remains less clear. Tetrahymena thermophila is an important model organism to evaluate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Most ABC transporter proteins are integral membrane proteins that act as ATP‐driven transporters 66 . In T. thermophila , increased activities of ABC transporters are associated with enhanced tolerance toward xenobiotics 67 . For instance, upregulation of membrane pump proteins (ABC‐transporters) enhanced the tolerance of T. thermophila to DDT by pumping out the toxicants to extracellular spaces and reducing ROS production 68 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ABC transporter proteins are integral membrane proteins that act as ATP‐driven transporters 66 . In T. thermophila , increased activities of ABC transporters are associated with enhanced tolerance toward xenobiotics 67 . For instance, upregulation of membrane pump proteins (ABC‐transporters) enhanced the tolerance of T. thermophila to DDT by pumping out the toxicants to extracellular spaces and reducing ROS production 68 .…”
Section: Discussionmentioning
confidence: 99%
“…66 In T. thermophila, increased activities of ABC transporters are associated with enhanced tolerance toward xenobiotics. 67 For instance, upregulation of membrane pump proteins (ABC-transporters) enhanced the tolerance of T. thermophila to DDT by pumping out the toxicants to extracellular spaces and reducing ROS production. 68 Here we have observed that some isoforms of ABC transporters were upregulated at a different dosage.…”
Section: Proteomic Response Of T Thermophila To Glyphosatementioning
confidence: 99%
“…SA, methane (CH 4 ), and WRKY DNA-binding protein 13 (WRKY13) transcription factor were suggested to be involved in the above process [30,111,112]. H 2 S regulated the activities of key enzymes and AsA-GSH cycle involved in ROS homeostasis to alleviate Cd-induced oxidative stress [113][114][115][116][117][118][119][120]. For example, H 2 S enhanced the activities of antioxidant enzymes, such as POD, CAT, APX, and SOD, and thereby decreased ROS accumulation [120].…”
Section: H 2 S Action In Plant Tolerance Against CD Stressmentioning
confidence: 99%
“…Increasing evidence demonstrates that H 2 S also regulates Cd uptake and translocation in plants [30,117,119,121]. H 2 S enhanced the expression of genes encoding metallothionein (MTs) and phytochelatin (PCS) in Arabidopsis roots [117].…”
Section: H 2 S Action In Plant Tolerance Against CD Stressmentioning
confidence: 99%
See 1 more Smart Citation